Follow-up study of high-dose praziquantel therapy for cerebral sparganosis. - Peng Zhang; Yang Zou; Feng-Xia Yu; Zheng Wang; Han Lv; Xue-Huan Liu; He-Yu Ding; Ting-Ting Zhang; Peng-Fei Zhao; Hong-Xia Yin; Zheng-Han Yang; Zhen-Chang Wang (PLoS Neglected Tropical Diseases, 2019)
Background Cerebral sparganosis is the most serious complication of human sparganosis. Currently, there is no standard for the treatment of inoperable patients. Conventional-dose praziquantel therapy is the most reported treatment. However, the therapeutic outcomes are not very effective. High-dose praziquantel therapy is a useful therapeutic choice for many parasitic diseases that is well tolerated by patients, but it has not been sufficiently evaluated for cerebral sparganosis. This study aims to observe the prognoses following high-dose praziquantel therapy in inoperable patients and the roles of MRI and peripheral eosinophil absolute counts during follow-up. Methodology Baseline and follow-up epidemiological, clinical, radiological and therapeutic data related to 10 inoperable patients with cerebral sparganosis that were treated with repeated courses of high-dose praziquantel therapy, with each course consisting of 25 mg/kg thrice daily for 10 days were assessed, followed by analyses of the prognoses, MRI findings and peripheral eosinophil absolute counts. Principal findings Baseline clinical data: the clinical symptoms recorded included seizures, hemiparesis, headache, vomiting and altered mental status. Peripheral blood eosinophilia was found in 3 patients. The baseline radiological findings were as follows. Motile lesions were observed in 10 patients, including aggregated ring-like enhancements, tunnel signs, serpiginous and irregular enhancements. Nine of the 10 patients had varying degrees of white matter degeneration, cortical atrophy and ipsilateral ventricle dilation. The follow-up clinical data were as follows. Clinical symptom relief was found in 8 patients, symptoms were eliminated in 1 patient, and symptoms showed no change from baseline in 1 patient. Peripheral blood eosinophilia was found in 2 patients. The follow-up radiological findings were as follows. Motile lesions that were transformed into stable, chronic lesions were found in 8 patients, and motile lesions that were eliminated completely were found in 2 patients. Conclusions High-dose praziquantel therapy for cerebral sparganosis is effective. The radiological outcomes of motile lesions are an important indicator during the treatment process, especially during follow-ups after clinical symptoms have improved. Peripheral eosinophil absolute counts cannot be used as an effective prognostic indicator.